Potential flora of Arunachal Pradesh for landscaping - Tomar, Krishna S; Kumar, Prabhat; Shakywar, R C; Pathak, M (Indian Horticulture, 2015)
Flower basket is very narrow in landscape gardening and it act as deterrent for landscape architect to visualise his/ her dream in to reality. The native plants which are having potential to qualify as landscape plants must be identified, characterized, conserve and popularized by evolving horticultural technology like propagation and cultural practices for better growth and development. There is still scope to popularize these neglected and underutilized ornamental plants in Arunachal Pradesh as well as other parts of northeastern states. Genetic erosion and extinctions may be controlled through exploration and collection of these species. It is high time to conserve these ornamental species through in situ or ex situ methods and sensitize the local people about their aesthetic value.